Sustainable Asia:Supporting the Transition to Sustainable Consumption and Production in Asian Developing Countries - Kartika Anggraeni (World Scientific Publishing Co., 2017)
In the emerging narrative of sustainable development in Asia, the essential challenge is to reduce the use of natural resources and environmental degradation alongside the increasing demand for goods and services. To achieve this, Sustainable Consumption and Production (SCP), one of the Sustainable Development Goals (SDGs) adopted by the United Nations in 2015, aims at reconciling the three goals of minimising the extraction of natural resources from the environment, limiting waste and emissions over the life cycle of goods and services and improving human development and wellbeing. Sustainable Asia: Supporting the Transition to Sustainable Consumption and Production in Asian Developing Countries provides an overview and analysis of the current status of SCP in Asian developing countries. The book focuses on projects supported by the EU-funded SWITCH-Asia Programme, a regional development cooperation programme promoting the adoption of SCP practices among small and medium-sized enterprises (SMEs) and consumer groups in Asia since 2007. For readers looking for a comprehensive introduction to the topic of SCP together with a detailed analysis of the current developmental situation in various Asian developing countries and key sectors such as manufacturing, tourism, renewable energy and agriculture, this book is an invaluable tool. The book examines in detail the SCP approaches and innovative solutions demonstrated by the SWITCH-Asia supported projects in Asia and thus serves as a reference for practitioners, researchers and policymakers alike.